Iowa Ornithologists' Union, Quarterly field report, fall 1993 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Quarterly field report for the fall of 1993 compiled by Thomas H. Kent and James L. Fuller. Plustek - flatbed